Impacts of marine and freshwater aquaculture on wildlife: a global meta‐analysis. (14th August 2018) - Barrett, Luke T.; Swearer, Stephen E.; Dempster, Tim
Abstract: The global expansion of aquaculture has raised concerns about its environmental impacts, including effects on wildlife. Aquaculture farms are thought to repel some species and function as either attractive population sinks ('ecological traps') or population sources for others. We conducted a systematic review and meta‐analysis of empirical studies documenting interactions between aquaculture operations and vertebrate wildlife. Farms were associated with elevated local abundance and diversity of wildlife, although this overall effect was strongly driven by aggregations of wild fish at sea cages and shellfish farms (abundance: 72×; species richness: 2.0×). Birds were also more diverse at farms (1.1×), but other taxa showed variable and comparatively small effects. Larger effects were reported when researchers selected featureless or unstructured habitats as reference sites. Evidence for aggregation 'hotspots' is clear in some systems, but we cannot determine whether farms act as ecological traps for most taxa, as few studies assess either habitat preference or fitness in wildlife. Fish collected near farms were larger and heavier with no change in body condition, but also faced higher risk of disease and parasitism. Birds and mammals were frequently reported preying on stock, but little data exist on the outcomes of such interactions for birds and mammals – farms are likely to function as ecological traps for many species. We recommend researchers measure survival and reproduction in farm‐associated wildlife to make direct, causal links between aquaculture and its effects on wildlife populations.